Rovnost a zásluhovost v právu - Čurila, Dušan; Masarykova univerzita. Katedra právní teorie (2015)
Moja práca sa zaoberá rovnosťou a zásluhovosťou v práve. Tieto základné kritériá spravodlivosti majú v práve veľký význam. Obe kritériá charakterizujem v práci najprv z právno-teoretického hľadiska. V ďalšej časti práce sa venujem obom kritériám a ich aplikácii v niektorých právnych predpisoch českého a slovenského právneho poriadku a v judikatúre vybraných českých a slovenských súdov. Kritérium rovnosti analyzujem v judikatúre Najvyššieho súdu Českej republiky, Najvyššieho súdu Slovenskej republiky a Najvyššieho správneho súdu Českej republiky. Kritérium zásluhovosti analyzujem v judikatúre Ústavného súdu Českej republiky, Ústavného súdu Slovenskej republiky a Najvyššieho správneho súdu Českej republiky.
My thesis deals with equality and merit in law. These fundamental criteria of justice have enormous importance in law. First of all, I characterize both criteria in my thesis in law-theory aspects. In next part of my thesis I offer an analyse of both criteria and their application in some acts of Czech and Slovak law system and in the case law of some Czech and Slovak courts. I analyze the criterion of equality in the case law of the Supreme Court of Czech Republic, in the case law of the Supreme Court of the Slovak Republic and the Supreme Administrative Court of the Czech Republic. After that I analyze the criterion of merit in the case law of the Constitutional Court of the Czech Republic, in the case law of the Constitutional Court of the Slovak Republic and of the Supreme Administrative Court of the Czech Republic.
Rigorózní práce (JUDr.)--Masarykova univerzita, Právnická fakulta, 2015
Německé resumé
Keywords: rovnost (kategorie); spravedlnost; equality; justice; rigorózní práce; doctoral dissertations